1999
DOI: 10.1038/46058
|View full text |Cite
|
Sign up to set email alerts
|

A plant regulator controlling development of symbiotic root nodules

Abstract: Symbiotic nitrogen-fixing root nodules on legumes are founded by root cortical cells that de-differentiate and restart cell division to establish nodule primordia. Bacterial microsymbionts invade these primordia through infection threads laid down by the plant and, after endocytosis, membrane-enclosed bacteroids occupy cells in the nitrogen-fixing tissue of functional nodules. The bacteria excrete lipochitin oligosaccharides, triggering a developmental process that is controlled by the plant and can be suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
707
0
18

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 806 publications
(749 citation statements)
references
References 26 publications
24
707
0
18
Order By: Relevance
“…Reducing the level of HMGR1 by inhibitor lavastatin or RNA interference (RNAi) expression results in a drastic decrease in nodulation in M. truncatula (Kevei et al, 2007). SIP1 binds the promoter of the NIN (for nodule inception) gene (Zhu et al, 2008), which is required for rhizobial recognition, IT formation, and nodule primordial initiation (Schauser et al, 1999). These results suggest that SymRK may form protein complex with key regulatory proteins of downstream cellular responses.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Reducing the level of HMGR1 by inhibitor lavastatin or RNA interference (RNAi) expression results in a drastic decrease in nodulation in M. truncatula (Kevei et al, 2007). SIP1 binds the promoter of the NIN (for nodule inception) gene (Zhu et al, 2008), which is required for rhizobial recognition, IT formation, and nodule primordial initiation (Schauser et al, 1999). These results suggest that SymRK may form protein complex with key regulatory proteins of downstream cellular responses.…”
mentioning
confidence: 88%
“…To investigate if nodulin gene expression was affected by SIE3 RNAi, we examined the expression levels of NIN and ENOD40-2, two early nodulin genes implicated in the processes of rhizobial entrance, nodule initiation, and subsequent organogenesis (Schauser et al, 1999;Kumagai et al, 2006), as well as the expression of Lb (for leghemoglobin), a typical nodulin gene required for nitrogen fixation (Ott et al, 2005). Real-time PCR analysis showed that the expression levels of the two early nodulin genes (NIN and ENOD40-2), but not Lb, were reduced drastically in the SIE3 RNAi hairy roots, as compared with those in the control hairy roots ( Fig.…”
Section: Suppression Of Rhizobial Infection By Sie3 Rnaimentioning
confidence: 99%
“…Another gene with a potential role in N regulation of nodulation has recently been identified in Lotus japonicus (Schauser et al, 1999). This gene (Nin), which is required for the formation of infection threads and the initiation of nodule primordia, encodes a putative transcription factor with homology to the Mid protein in Chlamydomonas.…”
Section: Localized Responsesmentioning
confidence: 99%
“…This gene (Nin), which is required for the formation of infection threads and the initiation of nodule primordia, encodes a putative transcription factor with homology to the Mid protein in Chlamydomonas. Mid is a developmental regulator involved in determining mating type during gametogenesis (Ferris and Goodenough, 1997), and since gametogenesis in Chlamydomonas is induced by N limitation it has been postulated that Nin might play a role in N regulation of nodulation (Schauser et al, 1999). Recently it was shown that NO 3 − inhibited gametogenesis and the expression of two gamete-specific genes even in NR-deficient mutants of Chlamydomonas, indicating that the NO 3 − ion itself is providing the negative regulatory signal for the sexual differentiation of the alga (Pozuelo et al, 2000).…”
Section: Localized Responsesmentioning
confidence: 99%
“…This signaling cascade triggers Ca 2+ spiking in and around the nucleus. Decoding of this Ca 2+ signature by a Ca 2+ calmodulin-binding protein (DMI3) results in the activation of the transcription factors Nodulation Signaling Pathway1 (NSP1), NSP2, Ethylene-Responsive Binding Domain Factor Required for Nodulation1 (ERN1), and Nodule Inception (NIN; Schauser et al, 1999;Catoira et al, 2000;Borisov et al, 2003;Oldroyd and Long, 2003;Gleason et al, 2006;Andriankaja et al, 2007;Marsh et al, 2007;Middleton et al, 2007;Oldroyd and Downie, 2008). NSP2, ERN1, and NIN also play a role downstream of the cytokinin signaling to trigger cortical cell division (Tirichine et al, 2007;Frugier et al, 2008).…”
mentioning
confidence: 99%